The Effect of Islamic Education Understanding Toward Gambling Behavior - Al Anhar; Muhamad Muhamad (Journal of Research in Islamic Education, 2019)
The process of human thought is determined by the situation and environment in which they live. Education is a continuous process in human life from the age of 0 (zero) to perfect human (adult). In the current era of globalization the world of education is faced with various kinds of challenges and problems. Among the problems are as the emergence of various kinds of juvenile deviations. Especially related to gambling. Talking about adolescents which are mainly related to gambling problems is very important and interesting to discuss. Because teenager is a National asset and a hope for the future of the nation and the state and religion.This experimental study aims at assessing the effect of Islamic education understanding on gambling activity. It was found that there was significant influence between Islamic education and gambling.